Biodegradation of methylene blue dye in a batch and continuous mode using biochar as packing media - Bharti V.; Vikrant K.; Goswami M.; Tiwari H.; Sonwani R.K.; Lee J.; Tsang D.C.W.; Kim K.-H.; Saeed M.; Kumar S.; Rai B.N.; Giri B.S.; Singh R.S. (My University, 2025)
Bacterial species for metabolizing dye molecules were isolated from dye rich water bodies. The best microbial species for such an application was selected amongst the isolated bacterial populations by conducting methylene blue (MB) batch degradation studies with the bacterial strains using NaCl-yeast as a nutrient medium. The most suitable bacterial species was Alcaligenes faecalis (A. faecalis) according to 16S rDNA sequencing. Process parameters were optimized and under the optimum conditions (e.g., inoculum size of 3 mL, temperature of 30 °C, 150 ppm, and time of 5 days), 96.2% of MB was removed. Furthermore, the effectiveness for the separation of MB combining bio-film with biochar was measured by a bio-sorption method in a packed bed bioreactor (PBBR) in which microbes was immobilized. The maximum MB removal efficiencies, when tested with 50 ppm dye using batch reactors containing free A. faecalis cells and the same cells immobilized on the biochar surface, were found to be 81.5% and 89.1%, respectively. The PBBR operated in continuous recycle mode at high dye concentration of 500 ppm provided 87.0% removal of MB through second-order kinetics over 10 days. The % removal was found in the order of PBBR>Immobilized batch>Free cell. The standalone biochar batch adsorption of MB can be described well by the pseudo-second order kinetics (R2 ≥ 0.978), indicating the major contribution of electron exchange-based valence forces in the sorption of MB onto the biochar surface. The Langmuir isotherm suggested a maximum monolayer adsorption capacity of 4.69 mg g−1 at 40 °C which was very close to experimentally calculated value (4.97 mg g−1). Moreover, the Casuarina seed biochar was reusable 5 times. © 2019